2022
DOI: 10.3390/ani12101268
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of Canine Heartworm in Spain

Abstract: The climate of Spain has favourable characteristics for the development of D. immitis in dogs, being an endemic country. Given that vector-borne diseases are spreading rapidly through Europe, due to factors such as climate change, the expansion of vectors and the increased mobility of reservoir animals, the aim was to update the epidemiology of heartworm in dogs and analyse the results based on climate and other epidemiological and geo-environmental factors. To this aim, 9543 blood samples from dogs from all p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 32 publications
2
6
0
Order By: Relevance
“…immitis progressively increased in central and southern Italy regions in the last decade ( 17 ). Worthy of note, a similar picture has recently been observed in other Mediterranean countries such as Spain ( 25 ). On the other hand, D .…”
Section: Discussionsupporting
confidence: 83%
“…immitis progressively increased in central and southern Italy regions in the last decade ( 17 ). Worthy of note, a similar picture has recently been observed in other Mediterranean countries such as Spain ( 25 ). On the other hand, D .…”
Section: Discussionsupporting
confidence: 83%
“…Spain and Portugal have traditionally been considered endemic countries, although not all areas of the Iberian Peninsula have been studied [5]. In Spain, the prevalence of D. immitis in dogs is 6.47% [13], and the seroprevalence in cats is 9.4% [14]. In the case of Portugal, published studies in dogs provide prevalence values ranging from 0.9% to 27.3%, being higher in the south [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a previous study carried out in the Canary Islands demonstrated the hyperendemic status of the islands, showing a seroprevalence of 18.1%, although a remarkable disparity was found when evaluating the results by island separately, which ranged from 0% in El Hierro to 24.1% in Tenerife [18]. Moreover, on the island of Gran Canaria, a seroprevalence of 18.3% was recorded in cats in 2004 [119], so the results of the latest studies being 21.3% in 2016 [18] and 22.9% in 2022 [17] demonstrates a slow but constant increase in feline seroprevalences [120]. Furthermore, all studies concluded that the presence of feline seropositivity was linked to the presence of canine heartworm.…”
Section: Feline Heartwormmentioning
confidence: 96%
“…In the Canary Islands, previous research has shown higher prevalence in the past, demonstrating that prevalence has gradually decreased over the years, probably due to prevention campaigns carried out by veterinarians [18]. However, disease is currently present in Lanzarote, previously considered free of heartworm [17]. Other studies carried out in northern and centre Spain have reported a prevalence of 0.18 and 7.19% for D. immitis, respectively [19,20].…”
Section: Endemic Areas (■) and Sporadic Cases Reported (■) )mentioning
confidence: 96%
See 1 more Smart Citation